The Aesthetics of the Postpornographic Body in Painting after Postmodernity - Magaña Villaseñor, Luz del Carmen (2018)
This essay deals with the idea of how body is conceived in painting from works of post-pornography. In this movement, sex is not seen as a profitable business, but it is possible to see it, reproduce it, and make art from the body, skin, fluids, and orifices, in a sense of the obscene and abject. But it also contemplates an aesthetic sense from which new options in discourse begin to be forged. In post-pornography, the idea of pleasure arises not only for pure bodily pleasure, but for its aesthetic pleasure. There is, then, a difference between eroticism and pornography, that is, an alternate place for these two topics where post-pornography is located. An analysis is made of the place of painting within this movement by taking some artists as reference. Sexual and pornographic corporeality are claimed in the work from painting, from its discourse, and from the re-signification of a concept that is known in a primary way, to create new meanings.